Tráfico ilegal de armas de fuego enfocado a la negociación con la guerrilla colombiana, incidiendo en la seguridad nacional ecuatoriana. - Sarchi Gómez, Erika Geovanna (2023)
The purpose of this study is to analyze the illegal trafficking of firearms focused on the negotiation with the Colombian guerrilla with an impact on Ecuadorian National Security. Thus, the starting point was the determination of the evolutionary context of illegal firearms trafficking in Ecuador, its regulations and consequences in social matters, demonstrating that, although Ecuador has not historically been a country that has had problems with the possession of firearms in the civilian area or has had a developed industry in this area, over time it has become an organized crime state, where the easy permeability of the borders and the absence of the government have allowed the promotion of negative aspects mainly for the society and the economy of the country. It was also possible to identify the role of the Colombian guerrilla and its influence as a threat to the national security of the Ecuadorian State, which is based fundamentally on the historical contexts of displacement and refuge by the Colombian population into Ecuadorian territory as a direct consequence of the guerrilla conflicts. However, the peace treaty signed by Colombia brought more violence to Ecuador, since the dissident guerrilla groups are supplied with illegal arms transported from Peru, which has turned the country into a strategic transit sector, causing chaos at the national level and creating a significant amount of collateral damage. Finally, the legal and juridical strategies and public policies of the Ecuadorian and Colombian governments to combat illegal firearms trafficking are described, which are, on the part of both countries, the corresponding Magna Carta, as well as the provisions of the respective Penal Code, in addition to laws and decrees whose purpose is to regulate everything related to the possession and carrying of arms and ammunition, among other items that are not authorized and that put national security at risk. Likewise, there are international instruments that are legally binding, such as the Arms Trade Treaty, the Firearms Protocol, among others, which imply a formal process of adherence and compliance by the States.